Sexo e sexualidade na editoria “amor (ou quase isso)”: efeitos de sentidos - Silva, Renan Fabrício Lorenzatto da (2020)
The themes of sex and sexuality, nowadays, can be observed in magazines, television programs, internet etc. Having sex for pleasure has been linked to sin and whoever did it, after death, would live forever in hell. It took us many years to have the “freedom” we have today to address these issues. One of the current media that has addressed this topic is Cosmopolitan magazine, formerly Nova magazine which is aimed at working women, is young and independent. The magazine presents itself as a publication that addresses controversial topics such as masturbation, sex, betrayal, etc., targeting classes A, B and C. Based on the French-oriented Discourse Analysis, this research aims to analyze how a discursive memory about women and their sexuality works, which production conditions support and allow such sayings and to which discursive formations the Cosmopolitan magazine “Amor (ou quase isso)” is affiliated. In addition, we will seek to understand how the issue of sex and sexuality is approached in its editorial, realizing to which woman the magazine speaks and where that woman is inserted. As a theoretical basis, authors Pêcheux (2008), Orlandi (2013) and Del Priore (2011) were used in questions about women. Thus, this research will contribute both to studies on sex and sexuality, as well as to studies related to journalistic discourses. Cosmopolitan magazine comes as a corpus for being a magazine of national circulation and of world renown, materializing how the discourses about sex and sexuality have been approached in the media, especially in print.